Professional standards for teaching mathematics - National Council of Teachers of Mathematics (Reston : Virginia : National Council of teachers of mathematics, 1991)
Addresses professional mathematics teaching on the basis of two assumptions: teachers are primary figures in changing the way mathematics is taught and learned in schools, and change requires that teachers have long-term support and adequate resources.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching -- Standards